Pengaruh Literasi Zakat, Transparansi, dan Akuntabilitas terhadap Preferensi Muzakki dalam Memilih Lembaga Zakat - Afifah Fitriani; Khusnul Hidayah (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to obtain empirical evidence that zakat literacy, transparency, and accountability can influence muzakki's interest in choosing a zakat institution. The dependent variable in this study is the preference of muzakki who choose to distribute zakat in state zakat institutions or private zakat organizations. The independent variables in this study are zakat literacy, transparency, and accountability. Zakat literacy, transparency, and accountability are measured using a 5-point Likert scale. The population in this study are all muzakki who distribute zakat at zakat institutions. Based on the simple random sampling method, the samples obtained were 56 samples that met the criteria. The analytical method used is multiple linear regression analysis. The results of the study show that zakat literacy and accountability have a significant effect on muzakki's preferences in choosing zakat institutions, while transparency has no significant effect on muzakki's preferences in choosing zakat institutions. Muzakki's preferences are dominated by distributing zakat at the nearest mosque and distributing it directly to the recipients of zakat.